PEMBERDAYAAN KELOMPOK TANI SAWAH PAYO KABUPATEN TANAH DATAR DALAM PEMBUATAN RIZOKOMPOS DAN PESTISIDA NABATI - Yanti, Yulmira; Hamid, Hasmiandy; Santoso, Putra; Hermeria, Noveriza (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The Sawah Payo Nagari Gunung Rajo farmers group of Batipuh Subdistrict, Tanah Datar Regency has the potential in the production of organic fertilizers and vegetable pesticides because it is supported by the rest of the agricultural products and weeds of Tithonia diversifolia, Piper aduncum and livestock waste (animal waste) which overflow. Utilization of weed crop agricultural waste, whether livestock is still not optimal. The processing of agricultural and agricultural waste into compost carried out by most farmers in Nagari Gunung Rajo has not used the fermentation process, resulting in less than optimal quality and farmers' ignorance in utilizing plants that cause vegetable pesticides. The purpose of this farmer group empowerment activity is to provide knowledge about the process of making organic fertilizers and vegetable pesticides from the supply of raw materials, making bio-activators, and packaging of production results. The method used is structured training and direct practice in making organic fertilizer. The results obtained from this empowerment activity are farmer groups capable of making organic fertilizers and vegetable pesticides independently with a fairly good quality of production results. Keywords: Empowerment, organic fertilizer, botanical pesticide. ABSTRAK Kelompok tani Sawah Payo Nagari Gunung Rajo Kecamatan Batipuh, Kabupaten Tanah Datar mempunyai potensi dalam produksi pupuk organik dan pestisida nabati hal ini karena didukung oleh sisa hasil pertanian jerami dan gulma tanaman pahitan Tithonia diversifolia, Piper aduncum dan limbah peternakan (kotoran hewan) yang melimpah. Pemanfaatan limbah pertanian tanaman gulma, maupun peternakan masih belum maksimal. Pengolahan limbah pertanian dan peternakan menjadi kompos yang dilakukan oleh sebagian besar petani di Nagari Gunung Rajo belum menggunakan proses fermentasi, sehingga hasilnya dan kualitasnya kurang maksimal serta ketidaktahuan petani dalam memanfaatkan tanaman yang berpotensi sebagai pestisida nabati. Tujuan kegiatan pemberdayaan kelompok tani ini adalah memberikan pengetahuan tentang proses pembuatan pupuk organik dan pestisida nabati dari penyedian bahan baku, pembuatan bio-aktivator, dan pengemasan hasil produksi. Metode yang digunakan dengan pelatihan terstruktur dan praktik langsung pembuatan pupuk organik. Hasil yang diperoleh dari kegiatan pemberdayaan ini adalah kelompok tani mampu membuat pupuk organik dan pestisida nabati secara mandiri dengan kualitas hasil produksi yang cukup baik. Kata kunci: Pemberdayaan, pupuk organik, pestisida nabati.